Hybrid high performance supercapacitor based on zeolitic imidazolate frameworks-67-derived nano-structure NiCo2S4. (29th March 2023) - Wang, Xianchao; Xu, Yongchao; An, Xinhao; Xu, Enze; Liu, Junnan; Zhou, Chunliang; Li, Weirong; Chen, Ye; Wang, Guiling
Abstract: In this work, NiCo2 S4, nickel-cobalt layered double hydroxides (NiCo-LDH) and CoS2 electrodes are successfully prepared by using ZIF-67 as the precursor, the results show that NiCo-LDH and NiCo2 S4 are nano-flower-like structures and CoS2 exhibits a nano-cage structure. The electrochemical properties of the hybrid supercapacitor assembled with NiCo2 S4 and activated carbon (AC) as electrodes were tested. As the positive electrode of NiCo2 S4 //AC hybrid supercapacitor, the NiCo2 S4 electrode has the largest specific capacity of 2934 mAh g −1 at a current density of 1 A g −1 . The NiCo2 S4 //AC capacitor generates the highest energy density of 38.8 Wh kg −1 when the power density is 993.0 W kg −1 and has a nice cycling performance with a capacity retention rate of 81.2% after 10, 000 cycles at 5 A g −1 . Highlights: Nano-flower-like structures NiCo2 S4 is successfully prepared by using ZIF-67 as the precursor. NiCo2 S4 shows nice performance as the cathode of NiCo2 S4 //AC (activated carbon) hybrid supercapacitor. NiCo2 S4 //AC (activated carbon) hybrid supercapacitor shows practical potential.